SEMIOTIKA FOTOGRAFI â€œHUJAN 3 JAM, JALAN MARTADINATA JADI KOLAMâ€ JAWA POS RADAR MALANG - Wicaksana, Yudistira Satya Wira; Artharini Koesanto, Stefani Made Ayu (Jurnal Ranah Komunikasi, 2024)
Sewer dysfunction during rainfall causes flooding on the streets, occurred in Malang City in March 2023. The incident was captured by a photojournalist and incorporated into a journalistic work. The photo was published on the official Instagram account @jawaposradarmalang of the local mass media, Jawa Pos Radar Malang. The photojournalistic image serves as a visual message containing meanings conveyed through codes or signs. The purpose of research is to understand the representation of the drainage issue depicted in the photojournalism for social criticism. The interpretive paradigm is employed through descriptive writing. The theory utilized is Roland Barthes' semiotics, consisting of its basic framework and derived procedures for analysis. Its denotative meaning is that water is overflowing from the sewer onto the road, allowing someone to swim. Its connotative meaning is that the flooded streets indicate poor absorption and reflect the government's inadequate performance in managing the drainage system, as well as the community's disregard for proper waste disposal. The myth surrounding it is that the drainage system and road sewers are crucial infrastructures supporting urban planning, public health, and economic mobility.